Diversification during Hard Times. Issue 2 (3rd April 2023) - Attig, Najah; Sy, Oumar
Abstract: Using a large sample of stocks from 48 developed and emerging markets over 1995 to 2021, we find evidence that suggests that international diversification is the best risk-reduction tool when all markets are considered. However, after the turn of the millennium, industrial diversification is the best alternative for funds limited to developed markets, especially when they are restricted to a region. Importantly, the benefits of diversification persist through hard times, such as the Asian financial crisis, the IT bubble burst, the global financial crisis, and the COVID-19 pandemic, demonstrating their countercyclicality and proving their value when investors need them the most.